The Effect of Motivation on Nurse Performance in Moderation with Nurse Credentials at PKU Muhammadiyah Kutowinangun Hospital in the Covid-19 Pandemic Era - Rio Dimas Sugiarta; Fitri Arofiati; Elsye Maria Rosa (Eduvest - Journal of Universal Studies, 2022)
Power health wrong the only one nurses in the current COVID-19 era work bear heavy load about many threat are you serious to health work . Burden work and problem mental health officer health in the COVID-19 pandemic has become attention . Problem this increase error medical and Dead patient as well as could lower performance officer health . Credential process also Becomes part important , because as base gift authority clinic to nurse , however on reality not yet fully done with good . Type research used explanatory , with cross sectional design . Population study is whole nurse at PKU Muhammadiyah General Hospital Kutowinangun as many as 58 people. Technique taking sample i.e. total sampling, i.e. whole registered nurse as employee permanent and already get credentials as many as 56 nurses . Instrument study use questionnaire . Data analysis using Structural Equation Modeling (SEM) analysis with PLS application . Results analysis influence direct show there is influence motivation to performance nurse , there influence credentials to motivation nurse , there influence credentials to performance nurse . Credentials capable moderate influence motivation work to performance nurse at PKU Muhammadiyah General Hospital Kutowinangun